The Role of E-Commerce in Escalation of Digital Economy in The New Normal Era Based on Law Number 27 of 2022 Concerning Personal Data Protection - Tasya Safiranita; Ahmad M. Ramli; Denidah Olivia; Ferry Gunawan C.; Ega Ramadayanti (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
The phenomenon of the spread of the Novel Coronavirus Disease (Covid-19) globally and thoroughly has transformed the trend of society, including the people of Indonesia. The tendency of individual behavior in buying and selling transactions is transformed from outside the internet network (offline) to inside the internet network (online). The level of comfort and convenience of the public in accessing and choosing various types of products online through electronic systems has given birth to new tendencies and habits in the e-Commerce landscape and has the potential to remain relevant even after the pandemic is over.. However, problems have arisen related to e-Commerce user data which has experienced many leaks so their activities tend to be insecure. If in the e-commerce transactions a sense of security and legal certainty is not guaranteed, it is feared that its development will stagnate. The research uses normative juridical methods and analytical descriptive types that explain the relationship between the Covid-19 health crisis and its impact on the tendency of people to conduct electronic buying and selling transactions where there is a shift in demand from physical retail to e-Commerce during the New Normal period. From this study, it was found that e-Commerce plays a major role in helping the community to remain active in online buying and selling transactions even in the post- pandemic period where legal protection is guaranteed for their activities. As for the legal regime that regulates the protection of personal data, it can help optimize the acceleration of e-Commerce with responsibility and principles of safety and security in serving consumers.